Are Group Settings Intoxicating? Groups, Alcohol, and the Situational Dynamics of Violence - Lantz, Brendan (Criminal justice and behavior, 2025)
Research consistently demonstrates that both group offending and alcohol use change the anticipated rewards and consequences of offending, often exacerbating violent outcomes. Alcohol use is also a common feature of group delinquency and offending. Yet, scholars have yet to examine the interaction of these features of crime. Following this, this study investigates the interactive effects of co-offending and alcohol use on the severity of violent crimes using National Incident-Based Reporting System (NIBRS) data. We find that the risk of serious injury is significantly higher in both crimes involving co-offending and crimes in which the suspects were using alcohol. The combination of co-offending and alcohol use intensifies this effect, even more so when the incident involves younger or male suspects. Intoxicated solo offenses, however, are strikingly similar to group offenses not involving alcohol in their propensity for injury, a finding that has significant theoretical implications for understanding the nature of group violence.